Predicting the Efficacy of HER2-Targeted Therapies: A Look at the Host - Di Modica, Martina; Tagliabue, Elda; Triulzi, Tiziana (Disease Markers, 2017)
HER2 is overexpressed in 20% of invasive breast cancers (BCs) and correlates with a more aggressive disease. Until the advent of targeted agents, HER2 was associated with worse outcomes. Rationally designed HER2-targeted agents have been developed and introduced into clinical practice for women with HER2-amplified BC, improving disease-free and overall survival for primary and metastatic tumors. Trastuzumab, a recombinant humanized anti-HER2 monoclonal antibody, combined with chemotherapy, remains the standard of care for patients with HER2-positive BCs. However, many patients do not respond to this agent, whereas newer drugs have proven to be efficacious in clinical trials. The identification of biomarkers that select sensitive tumors and patients who will benefit from these new agents would help the incorporation of these therapies, limiting the risk of side effects and overtreatment and improving the outcomes of all patients with early-stage HER2-positive BC. We review the mechanisms of action of HER2-targeting agents, focusing on the involvement of the immune system and related predictive biomarkers.